(untitled) (Marketing Journal, 2025)
In modern economic conditions, the importance of innovative management methods and technological approaches for enterprises is increasing. The article examines theoretical and practical approaches to enhancing management efficiency and analyzes advanced fo reign experiences. Key aspects such as the implementation of digital technologies, improvement of labor productivity, application of innovative 148 management principles, and efficient resource management are highlighted. The research results indicate that an effective management system is a crucial factor in increasing enterprise competitiveness and ensuring economic growth.